PENERAPAN PERMAINAN TRADISIONAL ENGKLEK DALAM UPAYA MENSTIMULASI ASPEK PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI RA Al-IKHWAN KOTA TASIKMALAYA - Nurlela, Ruri; Nurul Aida, Depon; Muthmainah, Ai Siti (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2023)
The Traditional games are a form of children's play that circulate orally among members of a particular collective, are traditional in form and passed down from generation to generation, and have many variations. One of the traditional games that has stimulating value is engklek. Engklek is a game of jumping or tiptoeing on one foot into boxes. However, in this era, the game of engklek is very rarely played by children. This is caused by developments in the times that have taken away children's interest and interest in the traditional game of engklek. In fact, if we observe the traditional game of engklek, it can stimulate various aspects of a child's development. This research is included in qualitative descriptive case study research. The data collection technique in this research was carried out using documentation techniques. To get a more detailed picture of the state of the research setting, researchers used observation techniques. The application of the traditional engklek game to children aged 4-5 years at RA Al-Ikhwan Tasikmalaya is able to stimulate aspects of children's social emotional development. This is proven by the results of research that has been carried out that the level of achievement of social emotional development for group A children at RA Al-Ikhwan is Developing According to Expectations (BSH) and BSB (Developing Very Well).